2014
DOI: 10.7773/cm.v40i3.2436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental changes on picophytoplankton and bacteria in Daya Bay, South China Sea

Abstract: Environmental changes driven by intense human disturbance and natural processes govern the abundance and distribution characteristics of two picophytoplankton groups (Synechococcus and picoeukaryotes). Picophytoplancton and high DNA (HDNA) and low DNA (LDNA) bacterial groups, identified by flow cytometry, were assessed during the autumn monsoon transition period in Daya Bay (South China Sea). The abundance of Synechococcus and picoeukaryotes ranged from 2.16 × 104 to 1.45 × 105 cell mL–1 and from 0.78 × 103 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
1
5
0
4
Order By: Relevance
“…As in our research, Cheng et al (2013) found a negative correlation between the levels of dissolved oxygen and the density of E. coli; wetland aeration favored the development of E. coli predators and promoted the photooxidative damage. In Daya Bay (China), the presence of bacteria and microalgae were mainly associated with the concentration of nutrients (nitrates, ammonia, and silicates), which are highly impacted by anthropogenic activities, whereas dissolved oxygen showed a lower correlation (Wu et al 2014). In regard to pH, the values obtained for the samples from all the SS comply with the guidelines given in NOM-001-ECOL-1996 (pH = 5-10), which establishes the permissible maximum limits of pollutants in wastewater discharges in national waters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As in our research, Cheng et al (2013) found a negative correlation between the levels of dissolved oxygen and the density of E. coli; wetland aeration favored the development of E. coli predators and promoted the photooxidative damage. In Daya Bay (China), the presence of bacteria and microalgae were mainly associated with the concentration of nutrients (nitrates, ammonia, and silicates), which are highly impacted by anthropogenic activities, whereas dissolved oxygen showed a lower correlation (Wu et al 2014). In regard to pH, the values obtained for the samples from all the SS comply with the guidelines given in NOM-001-ECOL-1996 (pH = 5-10), which establishes the permissible maximum limits of pollutants in wastewater discharges in national waters.…”
Section: Discussionmentioning
confidence: 99%
“…Las principales actividades económicas de Sinaloa dependen de abundates recursos hídricos y de la calidad del agua (CONAPESCA 2012). Hoy en día se conoce que el agua contaminada de los canales de drenaje agrícola afecta de manera negativa la vida acuática y terrestre en Sinaloa (Escobedo-Urías et al 1999, Haws et al 2006, Ochoa Izaguirre y Soto-Jiménez 2013), México y el mundo (Bagordo et al 2012, Matano et al 2013, Riera et al 2013, Valdés et al 2014, Wu et al 2014. Por otra parte, los canales de drenaje pueden funcionar como humedales artificiales de flujo superficial y disminuir la contaminación del agua y sus efectos negativos, pero éstos deben transportar bajos flujos de agua para favorecer el establecimiento de las plantas acuáticas (Kadlec y Wallace 2009).…”
Section: Water Sampling and Analysisunclassified
See 3 more Smart Citations